Why man creates man - the measure of all things. (Mount Kisco, N.Y. Center for Humanities, 1986)
Presents a survey of the creative accomplishments of man from the ancient civilizations of Mesopotamia to contemporary America. Includes works of art, dramatic narrative and excerpts from literture and music.
Keywords: Arts; Civilization; Art studies; Humanities